The Role of Women in Maintaining Family Income in Islamic Economy and Mubādalah Review - Aye Sudarto; Muhamad Bisri Mustofa; Siti Wuryan; Muhammad Saidun Anwar; Mustika Edi Santosa (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
One of the motivations for women to work in the public sector is to increase family income. Usually, the husband's income is insufficient to meet family needs, so some women work in this sector. This study aimed to describe the Islamic views and conditions of working women in the Kita Muslim Fashion Convection, Way Serdang District, Mesuji Regency, Lampung Province, in helping to increase family income. This study used a descriptive qualitative method with a phenomenological approach. Data sources consist of primary data from interviews and secondary data from research-supporting documents. At the same time, the data analysis model uses interaction analysis. The results of this study are that Islam positions women as equal to men, where they also have rights and responsibilities within the family. Husband and wife can complement each other's tasks in the family. Women can replace or share the burden of meeting family needs with their partners. This phenomenon is similar to the women workers at the Kita Muslim Fashion Convection, Way Serdang District, Mesuji Regency, Lampung Province, who contribute to helping the family economy so that household needs can be fulfilled.